Graphical Basis Of Girikh Used In Traditional Applied Decorative Art Of Central Asia In The 9-15th Centuries. - Ruziyevich, Sobirov Tolib; Karimovich, Omonov Qavmiddin (The journal of contemporary issues in business and government, 2021)
In this article, the process of using effective methods and designing engineering graphics in the teaching of Sciences for the purpose of wide application of geometrical patterns of Central Asian scientists of 9-15th centuries in the fields of National Art and architecture and the basis of girikh patterns, application of several methods in modern architecture, construction and restoration is analysed.